2022
DOI: 10.1111/joim.13453
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Covid‐19‐vaccination adverse events and healthcare utilization among individuals with or without previous SARS‐CoV‐2 infection

Abstract: Background Post‐marketing pharmacovigilance data are scant on the safety of Covid‐19 vaccines among people with previous SARS‐CoV‐2 infection compared with ordinary vaccine recipients. We compared the post‐vaccination adverse events of special interests (AESI), accident and emergency room (A&E) visit, and hospitalization between these two groups. Methods We conducted a retrospective cohort study using a territory‐wide public healthcare database with population‐based vaccination records in Hong Kong. Results In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…However, our previous publications have shown that vaccine recipients in Hong Kong were younger, healthier, and on fewer medications than unvaccinated people during the observation period. 12 , 15 , 16 Hence, our findings may not be fully applicable to people in poor health. Nevertheless, a “healthy vaccine recipient effect” is unlikely to affect our results because of the within-person comparison nature of the SCCS.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, our previous publications have shown that vaccine recipients in Hong Kong were younger, healthier, and on fewer medications than unvaccinated people during the observation period. 12 , 15 , 16 Hence, our findings may not be fully applicable to people in poor health. Nevertheless, a “healthy vaccine recipient effect” is unlikely to affect our results because of the within-person comparison nature of the SCCS.…”
Section: Discussionmentioning
confidence: 90%
“…Firstly, our study reported a low rate of chronic liver disease among vaccinated individuals with incident ALI so it is possible that some underlying liver diseases may have been underdiagnosed. However, our previous publications have shown that vaccine recipients in Hong Kong were younger, healthier, and on fewer medications than unvaccinated people during the observation period (12,15,16).…”
Section: Ali Risk In Comparison With Patients With Sars-cov-2 Infectionmentioning
confidence: 93%
See 1 more Smart Citation
“…EMRs from the HA were linked with the DH vaccination records using de-identified non-reversible pseudo-ID to protect patient privacy. The database has been use for several COVID-19 vaccine safety assessment in HK [ 8 , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ].…”
Section: Methodsmentioning
confidence: 99%
“…All prescriptions dispensed by HA pharmacies are recorded. These two linked data sources have been recently used to conduct population-based pharmacovigilance studies of COVID-19 vaccines [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Data Sourcementioning
confidence: 99%